TREND ANALYSIS OF FINANCIAL PERFORMANCE OF LOCAL GOVERNMENT (Studies in the District and City in the province of West Nusa Tenggara Year 2011-2014) - Kurniawan, Dhody (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research is quantitative descriptive. This study aims to analyze the performance of the financial district and the city in West Nusa Tenggara province in 2011-2014 seen from Independence ratio, dependency ratio, ratio of Harmony, Contributions PAD Regional Finance, Growth PAD, PAD Ratio Effectiveness, Efficiency Ratios Financial, ratios Fiscal Autonomy Degrees and capability Index Routine. Based on the results of this research is that the independence of the District and City in NTB Province is still very low, The dependency ratio is still very high, harmony ratios for operating and capital expenditures are still fluctuating, the trend growth rate of the most stable PAD is North Lombok, whereas for the district and other cities experienced fluctuating revenue growth, PAD contribution ratio trend is best shown by the City of Mataram and Lombok Utara, effectiveness ratio of PAD acceptance belonged highly effective for the city of Mataram and Lombok Utara, for other areas still volatile, financial efficiency ratio is still very low for the District and City in NTB, while the ratio of the degree of fiscal autonomy of County and City in NTB province still lacking, and the ratio of the routine capability index average is still lacking.Keywords: Independence ratio, Contributions PAD Regional Finance, Growth PAD, Ratio Fiscal Autonomy Degrees and Capabilities Index Routine.